Digital connectivity and low earth orbit satellite constellations opportunities for Asia and the Pacific. - Garrity, John; Asian Development Bank (Manila,Philippines Asian Development Bank, [2021])
Satellite communication plays an important role in the global connectivity ecosystem. It connects rural and remote populations, provides backhaul connectivity to mobile cellular networks, and enables rapid communications for emergency and disaster responses. Low Earth orbit constellations may prove to be transformational to the connectivity landscape based on their global coverage and their suitability for areas not served by fiber optic cable networks. ADB developing member countries are well placed to benefit from this expansion of internet connectivity, especially small island developing states and landlocked developing countries.
Keywords: Information technology; Electronic book